2014
DOI: 10.3390/soc4010045
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Danger, Parental Monitoring, Harsh Parenting, and Child Aggression in Nine Countries

Abstract: Exposure to neighborhood danger during childhood has negative effects that permeate multiple dimensions of childhood. The current study examined whether mothers’, fathers’, and children's perceptions of neighborhood danger are related to child aggression, whether parental monitoring moderates this relation, and whether harsh parenting mediates this relation. Interviews were conducted with a sample of 1,293 children (age M = 10.68, SD = .66; 51% girls) and their mothers (n = 1,282) and fathers (n = 1,075) in ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 54 publications
2
27
0
1
Order By: Relevance
“…It is noteworthy that like the current results, prior cultural comparative work also pointed to similarities rather than differences between wealthy versus poorer countries in the direction and magnitude of the associations between chaos, neighborhood danger, harsher parenting, and child maladjustment (Evans & Wachs, ; Ferguson et al, ; Skinner et al, ; Wachs & Corapci, ). The similarity in effect sizes is particularly noteworthy, when one considers that there are much higher levels of poverty, crime, and social disarray in many LMICs compared to high‐income countries; this may alter risk and resilience processes, and the statistical effects detected in studies (Barry, Clarke, Jenkins, & Patel, ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…It is noteworthy that like the current results, prior cultural comparative work also pointed to similarities rather than differences between wealthy versus poorer countries in the direction and magnitude of the associations between chaos, neighborhood danger, harsher parenting, and child maladjustment (Evans & Wachs, ; Ferguson et al, ; Skinner et al, ; Wachs & Corapci, ). The similarity in effect sizes is particularly noteworthy, when one considers that there are much higher levels of poverty, crime, and social disarray in many LMICs compared to high‐income countries; this may alter risk and resilience processes, and the statistical effects detected in studies (Barry, Clarke, Jenkins, & Patel, ).…”
Section: Discussionsupporting
confidence: 74%
“…It is noteworthy that like the current results, prior cultural comparative work also pointed to similarities rather than differences between wealthy versus poorer countries in the direction and magnitude of the associations between chaos, neighborhood danger, harsher parenting, and child maladjustment (Evans & Wachs, 2010;Ferguson et al, 2013;Skinner et al, 2014;Wachs & Corapci, 2003).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…There may be bidirectional and interactive effects between negative parenting and externalizing behavior . Specifically, negative dyadic interchanges between a parent with abusive tendencies and a child with externalizing behavior promote aggressive behavior in both parties, leading to conduct problems in the child …”
Section: Discussionmentioning
confidence: 99%
“…Negative interactions with parents have a detrimental effect on the emotional and psychological development of children, increasing their risk for aggression, delinquency, withdrawal, and other behaviors symptomatic of conduct disorder. [51][52][53][54][55][56][57][58][59][60] Most studies on child maltreatment and subsequent antisocial behavior have been conducted in Western countries. The US National Comorbidity Survey demonstrated that physically punished children were 1.3 times more likely to develop psychological problems and antisocial behavior compared to controls.…”
Section: Marianomentioning
confidence: 99%